Drop Weight Testing Rig Analysis and Design - Shuaeib, Farag Mohamed; Wong, Shaw Voon; Tan, Kean Sheng; Salem Hamouda, Abdel Magid; Radin Sohadi, Radin Umar; Megat Ahmad, Megat Mohamad Hamdan (Universiti Putra Malaysia Press, 2004)
Crashworthiness studies are becoming increasingly important in mechanical design, particularly with the new advancement of the computer simulation codes. These studies generally require material and prototype testing for both modelling and validation. Large percentages of these studies lie on the limits of medium strain rate, which could be achieved by a drop weight test rig. Therefore, the drop weight test rig becomes an essential tool for such research activities besides the universal quasi-static testing machines. This paper is devoted to the analysis and design of the drop weight impact-testing rig. First, the different aspects of the mechanical design such as the propulsion, guidance, and frame layout, foundation and energy aspects are presented and discussed. Then, the basic types of data retrieval and analysis systems applicable for drop weight impact testing machines are presented and discussed. Data retrieval components considered in this study include the sensors for load, acceleration, and velocity measurements, image acquisition including high-speed cameras and PC-based image acquisition system, and data acquisition including oscilloscope or PC-based data acquisition system which utilizes an AID card and application software for visualizing and analyzing of the results. At the end of this article the designed and constructed test machine is presented as a case study.